ENHANCING STUDENTS’ ENGAGEMENT IN FLSP CLASS: THE IMPACT OF NEARPOD - Metaria; Muniroh, Siti; Zubaidi, Nanang (University of Muhammadiyah Malang, 2024)
This quasi-experimental study investigates the effectiveness of Nearpod, a student-response-system, on elevating student engagement in Foreign Language for Specific Purposes (FLSP) classes. Utilizing Nearpod's interactive features to deliver the materials and activities through a shareable link, the study aimed to create a dynamic and immersive learning experience. The study involved 74 students from an FLSP course, divided into control and experimental groups. The experimental group were taught using Nearpod while the control group received regular instructions. Engagement levels were measured using a self-report questionnaire based on Wang et al. (2016), encompassing four domains of student engagement. The Mann-Whitney U-Test revealed that Nearpod significantly increased overall student engagement (U = 263.500, p < .05). Notably, behavioral, emotional, and social engagement showed significant improvements, while cognitive engagement did not (U = 450.500, p > .05). This empirical results show that Nearpod significantly enhances overall student engagement and positively impacts behavioral, emotional, and social engagement in FLSP integrated classes. However, cognitive engagement remains unaffected, suggesting a need for further exploration of strategies to address this aspect.This research provides valuable insights for language instructors, highlighting the potential of technology to foster engaging and interactive learning environments.